Estimation of an Equilibrium Model With Externalities: Post‐Disaster Neighborhood Rebuilding - Fu, Chao; Gregory, Jesse (Econometrica, 2019)
We study the optimal design of subsidies in an equilibrium setting, where the decisions of individual recipients impose externalities on one another. We apply the model to the case of post‐Katrina rebuilding in New Orleans under the Louisiana Road Home rebuilding grant program (RH). We estimate the structural model via indirect inference, exploiting a discontinuity in the formula for determining the size of grants, which helps isolate the causal effect of neighbors' rebuilding on one's own rebuilding choices. We find that the additional rebuilding induced by RH generated positive externalities equivalent to $4950 to each inframarginal household whose rebuilding choice was not affected by the program. Counterfactual policy experiments find that optimal subsidy policies bias grant offers against relocation, with an inverse‐U‐shaped relationship between the degree of bias and the severity of damages from the disaster.